Cost-effectiveness of intrapleural use of tissue plasminogen activator and DNase in pleural infection: Evidence from the MIST2 randomised controlled trial. - Luengo-Fernandez, R; Penz, E; Dobson, M; Psallidas, I; Nunn, A; Maskell, N; Rahman, N (European Respiratory Society Publications, 2019)
The MIST2 trial showed that combined intrapleural use of tissue plasminogen activator (t-PA) and DNase was effective when compared to single agents or placebo. However, the treatment costs are significant and overall cost-effectiveness of combined therapy remains unclear.An economic evaluation of the MIST2 trial was performed to assess the cost-effectiveness of combined therapy. Costs included were those related to study medications, initial hospital stay, and subsequent hospitalisations. Outcomes were measured in terms of life-years gained. All costs were reported in Euros (€) and in 2016 prices.Mean annual costs were lowest in the tPA-DNase group (€10 605 for t-PA, €17 856 for DNase; €13 483 for placebo, €7248 for t-PA-DNase (p=0.209)). Mean 1-year life expectancy was: 0.988 for t-PA; 0.923 for DNase; and 0.969 for both placebo and t-PA-DNase (p=0.296). Both DNase and placebo were less effective, in terms of life-years gained, and more costly than t-PA. When t-PA-DNase was compared to placebo, the incremental cost per life-year gained of t-PA-DNase was €1.6 billion, with a probability of 0.85 of t-PA-DNase being cost-effective.This study demonstrates that combined t-PA-DNase is likely to be highly cost-effective. In light of this evidence, a definitive trial designed to facilitate a thorough economic evaluation is warranted to provide further evidence on cost-effectiveness of this promising combined intervention.